Low-Frequency Baltic Sea Level Spectrum - Medvedev, Igor; Kulikov, Evgueni (Frontiers in Earth Science, 2019)
This study examines the Baltic sea level spectrum in the interval of periods from a few months to decades. Effective statistical methods of time series analysis have been applied to the long-term data from 36 tide gauges in the Baltic Sea, the Danish straits, and southeastern part of the North Sea to examine the character of low-frequency sea level variability. Using the spectral and wavelet analyses, we obtained estimates of the magnitudes of the main long period components of the sea level oscillations with periods of 8.4, 7.76, 6.16, 2.5, 1.7, 1.2 yr and discussed their possible origin. The peak with a period of 255 days is revealed in both the sea level spectra of the Baltic Sea and in the spectra of atmospheric processes. It is more pronounced in the air pressure variations from atmospheric reanalyses, especially ERA-Interim and NCEP/CFSR. Wavelet analysis revealed high coherence between the sea level oscillations at different stations and also with the zonal wind component. The result of the study shows that the low-frequency sea level variability in the Baltic Sea is highly correlated with the zonal wind variations over the extensive shallow-water areas of the sea.